Exploring the molecular targets of fingolimod and siponimod for treating the impaired cognition of schizophrenia using network pharmacology and molecular docking - Chao Li; Chuanjun Zhuo; Xiaoyan Ma; Ranli Li; Ximing Chen; Yachen Li; Qiuyu Zhang; Lei Yang; Lina Wang (Schizophrenia, 2024)
Abstract The treatment of cognitive impairment in schizophrenia is an unaddressed need due to the absence of novel treatments. Recent studies demonstrated that fingolimod and siponimod have neuroprotective effects in several neuropsychiatric disorders; however, their pharmacological mechanisms are unclear. The objective of this study was to identify potential molecular mechanisms of fingolimod and siponimod for improving cognition of schizophrenia through network pharmacology and molecular docking. The putative target genes of ingredients, schizophrenia, and impaired cognition were obtained from online databases, including SwissTargetPrediction, PharmMapper, GeneCards, CTD, DisGeNET, and OMIM. A protein–protein interaction network was constructed to identify core targets. The DAVID database was used for GO and KEGG pathway enrichment analyses. An ingredient–target–pathway–disease network was constructed using Cytoscape. Finally, the interactions between ingredients and core targets were assessed with molecular docking. The analysis revealed 260 targets shared by fingolimod and siponimod, 257 unique targets for fingolimod, and 88 unique targets for siponimod. Two signaling pathways were involved in fingolimod-mediated improvements in the cognition of schizophrenia, including the PI3K-Akt and MAPK signaling pathways. The core targets that regulated these two pathways included IL1B, AKT1, TNF, IL6, INS, BCL2, and BDNF. The MAPK signaling pathway was involved in siponimod-mediated improvement in the cognition of schizophrenia. The MAPK pathway was regulated by three core targets, namely TNF, AKT1, and CASP3. Docking scores ranged from −5.0 to −10.4 kcal/mol. Our analysis revealed that fingolimod regulates the PI3K-Akt and MAPK signaling pathways via the core targets IL1B, AKT1, TNF, IL6, INS, BCL2, and BDNF, and siponimod regulates the MAPK signaling pathways via the core targets AKT1, TNF, and CASP3 to improve the cognition of schizophrenia. Our results provide potential targets and a theoretical basis for the design of new drugs to treat the impaired cognition of schizophrenia.